Prevalence of Primary Open Angle Glaucoma in Patients with Hypertension - Archana Pushpakaran; Sedhu P.A; Ashwati Sankar; Cyriac Kurien (Asian Journal of Medical Research, 2020)
Background: Glaucoma is the second most common cause of blindness worldwide. It is one of the leading causes of irreversible blindness in the adult population worldwide.Glaucoma is a progressive optic neuropathy. The present study was conducted to assess prevalence of primary open angle glaucoma in patients with hypertension.Subjects and Methods:This cross- sectional study was conducted in outpatient department of SreeNarayana Institute of Medical Sciences. A total of 100 patients with hypertension were included in the study. Prevalence of primary open angle glaucoma in patients with HTN was recorded.Results:Out of 100,59 were males and 41 were females. Among the 100 hypertensive patients, 5% of patients had POAG. Among POAG, 3 were males and 2 were females. The percentage of patients with IOP between 8-21 was 95%, I0P >21 was 5% in right eye. The percentage of patients with IOP in between 8-21 was 95%, IOP >21 was 5% in left eye.Conclusion:High myopia, hypertension, diabetes mellitus has been associated with POAG, however, direct and convincing evidences are still lacking.